2021
DOI: 10.7150/thno.64022
|View full text |Cite
|
Sign up to set email alerts
|

Pre-therapeutic microglia activation and sex determine therapy effects of chronic immunomodulation

Abstract: Modulation of the innate immune system is emerging as a promising therapeutic strategy against Alzheimer's disease (AD). However, determinants of a beneficial therapeutic effect are ill-understood. Thus, we investigated the potential of 18 kDa translocator protein positron-emission-tomography (TSPO-PET) for assessment of microglial activation in mouse brain before and during chronic immunomodulation. Methods: Serial TSPO-PET was performed during five months of chronic microglia modulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…In this regard, TREM2 may slow AD progression and reduce tau-driven neurodegeneration by restricting the degree to which β-amyloid facilitates the spreading of pathogenic tau [ 72 ]. Our observations also had similarities to serial preclinical studies in mouse models, where microglial activation was correlated with worse outcome parameters in the P301S tau model [ 61 ], but with improved spatial learning performance in PS2APP [ 73 , 74 ] and App NL-G-F [ 17 ] Aβ models. A clinical study in patients with AD also suggested that anterior temporal [ 11 C]PK11195 binding, a region with abundant tau but low Aβ deposition is associated with progressive cognitive decline [ 75 ].…”
Section: Discussionsupporting
confidence: 77%
“…In this regard, TREM2 may slow AD progression and reduce tau-driven neurodegeneration by restricting the degree to which β-amyloid facilitates the spreading of pathogenic tau [ 72 ]. Our observations also had similarities to serial preclinical studies in mouse models, where microglial activation was correlated with worse outcome parameters in the P301S tau model [ 61 ], but with improved spatial learning performance in PS2APP [ 73 , 74 ] and App NL-G-F [ 17 ] Aβ models. A clinical study in patients with AD also suggested that anterior temporal [ 11 C]PK11195 binding, a region with abundant tau but low Aβ deposition is associated with progressive cognitive decline [ 75 ].…”
Section: Discussionsupporting
confidence: 77%
“…The value of TSPO imaging in glioma was already determined in prognostication and detection of tumor heterogeneity ( 5 , 6 ). For back translation and mechanistic elucidation of observations in humans as well as for TSPO biomarker monitoring during experimental testing of therapeutics, animal models provide a tremendous value across brain diseases ( 2 , 7 , 8 ). First experimental glioblastoma investigations with murine GL261 in immunocompetent mice ( 9 ), human P3 in immunodeficient mice ( 10 ), and human U87 in immunodeficient rats ( 11 ) indicated feasibility of TSPO PET monitoring by different radiotracers.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it reduced the number of reactive astrocytes and microglia in APP/PS1 mice, thereby showing antiinflammatory action while still promoting phagocytosis of Aβ-plaques [9]. Additionally, more recent studies have shown a positive effect of pioglitazone treatment on behavior [24] as well as a reduction in inflammation as measured by the attenuation of the TSPO-PET signal in PS2APP and APP NL-G-F mice [25].…”
Section: Discussionmentioning
confidence: 92%